2018
DOI: 10.4236/psych.2018.92016
|View full text |Cite
|
Sign up to set email alerts
|

Myths and Misconceptions in Developmental and Neuro-Psychology

Abstract: The current study examined the prevalence of psychological myths and misconceptions in two areas of psychology: Developmental and Neuro-Psychology. In all 220 participants completed two questionnaires both derived from two recently published books, in which they rated to what extent, they thought various statements/facts about the brain and about child development were True or False. A large number of these myths were rated as True (Definitely or Partly) indicating the extent to which people had misconceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Interestingly, despite researchers not having reached a consensus regarding the exact effects of sugar on mood, it seems that the public strongly believes in the idea that sugar improves mood ('Why is sugar so addictive? ', 2013) and increases activity levels (especially in children; Furnham, 2018). Although it is difficult to pinpoint the exact pathways that have made the 'sugar rush' notion so widely influential in popular culture, the origins of this notion can be traced back to studies suggesting that consumption of CHOs may increase hyperactivity in children (Flora and Polenick, 2013;Rojas and Chan, 2005;Wolraich et al, 1995Wolraich et al, , 1994Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, despite researchers not having reached a consensus regarding the exact effects of sugar on mood, it seems that the public strongly believes in the idea that sugar improves mood ('Why is sugar so addictive? ', 2013) and increases activity levels (especially in children; Furnham, 2018). Although it is difficult to pinpoint the exact pathways that have made the 'sugar rush' notion so widely influential in popular culture, the origins of this notion can be traced back to studies suggesting that consumption of CHOs may increase hyperactivity in children (Flora and Polenick, 2013;Rojas and Chan, 2005;Wolraich et al, 1995Wolraich et al, , 1994Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the binary response format appears less sensitive to detecting the true rate of endorsement. In addition to the binary true-false response format, items have routinely been worded such that the correct answer for all the misconception statements in the questionnaire are either all false or all true (e.g., Furnham, 2018;Gardner & Dalsing, 1986;McCarthy & Frantz, 2016) which may make the instrument susceptible to response bias and demand characteristics. Given these limitations, continued attention directed toward improved myth measurement is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Many people hold the erroneous belief that psychological knowledge is largely based on common sense (Lilienfeld, 2012). As a corollary, additional misconceptions about psychological phenomena are widespread and frequently endorsed by the general public (Furnham, 2018; Furnham & Hughes, 2014) including college students (Gaze, 2014; Lyddy & Hughes, 2012). Among the various topics within psychology, misconceptions about mental illness rank as the most commonly endorsed (Gardner & Brown, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that prior education has rather limited benefits in this area. Furnham (2018) presented survey participants with a set of myths about the mind and brain, and found that participants' education level did not correlate with accurate identification of myths, and that background study, specifically of psychology, was also unrelated. However, Furnham acknowledged that his work did not delve especially deeply into the level and manner in which participants had previously studied psychology; the questions also did not focus just on memory.…”
Section: Introductionmentioning
confidence: 99%